On price competition with market share delegation contracts - Luca Lambertini; Michael Kopel (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2012)
We identify a mistake in the specification of the demand system used in the strategic delegation model based on market shares by Jansen et al. (2007), whereby the price remains above marginal cost when goods are homogeneous. After amending this aspect, we perform a profit comparison with the alternative delegation scheme à la Fershtman and Judd (1987)
Keywords: L13; 330